Dispositif Pédagogique Pour L’apprentissage Des Oxydations Respiratoires Et La Résolution De Problèmes Non Routiniers - Mathias Kyélem; Daniel Favre (International Journal of Evaluation and Research in Education (IJERE), 2014)
In the sixth option D Form classroom, breathing is considered in terms of respiratory gas exchange and bioenergetics. The syllabus is generally away from the concept of breathing as seen in social representations and elsewhere at school, which is close to the old conceptions in many respects. Former introduction to those old conceptions hinders students’ ability to relate the enzymatic processes they are learning and the knowledge acquired in lower classes from the study of nutritional functions. This makes it necessary to develop teaching methods likely to incite learning in other disciplines and favor knowledge transfer towards solving non-routine problems. An experiment was conducted in Burkina Faso taking into account these issues and using a pedagogical device implementing a method of learning through problem-solving and integrating error treatment by teachers and socio-cognitive debate. This device, developed by the LIRDEF’s Didactics and Socialization Department, University of Montpellier II, shows that when students’ autonomy and right to make errors are valued and their emotional security guaranteed, they make significant learning following confrontation of their arguments.DOI: http://dx.doi.org/10.11591/ijere.v3i4.6937